2017
DOI: 10.20950/1678-2305.2017v43n4p614
|View full text |Cite
|
Sign up to set email alerts
|

Produção de alface (Lactuca sativa) em efluentes de um cultivo de tilápias mantidas em sistema BFT em baixa salinidade

Abstract: This experiment evaluated the effect of salinity on growth performance of different lettuce cultivars (Lactuca sativa) in an aquaponics system with biofloc technology. The device contained two independent systems with two different salinities: 0 ppt and 3 ppt. Juvenile tilapia (Oreochromis niloticus) 6.1 kg m-3 and three varieties of lettuce: red leaf and smooth and crisp 20 plants m-2 were stored in the floating system. All fish performance parameters showed no statistical differences, except for the hepatoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 0 publications
1
16
2
7
Order By: Relevance
“…Rahman (2010), using effluents from biofloc, observed that lettuce growth was limited by suspended solids and indicated that filtration was necessary. However, Lenz, Durigon, Lapa, and Emerenciano (2017) used two settling tanks, a mechanical filter, and biofilter before using the biofloc residual in hydroponic units, but some solids passed to the hydroponic benches. In contrast, Barbosa (2017) found the benefits of implementing mechanical and biological filters using a BFT residual in lettuce growth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rahman (2010), using effluents from biofloc, observed that lettuce growth was limited by suspended solids and indicated that filtration was necessary. However, Lenz, Durigon, Lapa, and Emerenciano (2017) used two settling tanks, a mechanical filter, and biofilter before using the biofloc residual in hydroponic units, but some solids passed to the hydroponic benches. In contrast, Barbosa (2017) found the benefits of implementing mechanical and biological filters using a BFT residual in lettuce growth.…”
Section: Discussionmentioning
confidence: 99%
“…sativa ) and basil ( O . basilicum ); however, the use of effluents from BFT aquaculture with different trophic levels in hydroponics has been limited (Barbosa, 2017; Fimbres‐Acedo, 2015; Lenz et al., 2017; Pinho, 2018; Pinho et al., 2017; Rahman, 2010). Concerning our results, basil ( O .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melhores resultados para o cultivo con vencional pode ser explicado devido a maior estabilidade do solo, proporcionando maior conforto térmico para as plantas, e às raízes maior capacidade de se fixarem e aumentar sua capacidade de absorção de nutrientes. Lenz et al (2017), relataram que os parâmetros fitotécnicos para as variedades lisa e crespa em sistema aquaponico cultivados por 28 dias, foram superiores aos encontrados no presente estudo (43 dias de cultivo). Feuzer (2016) obteve resultados superiores em 27 dias de cultivo para as variedades lisa e crespa.…”
Section: Resultados E Discussõesunclassified
“…Esta melhora nos índices zootécnicos no tanque-rede por ser devido ao fato de que além da ração ofertada, os peixes deste sistema tinham acesso à alimentação natural, o que pode ter favorecido um melhor desempenho, principalmente na eficiência e conversão alimentar. Tilápias criadas em sistema aquapônico em diferentes salinidades 0ppt e 3ppt apresentaram resultados semelhantes ao presente estudo, porém com menos tempo de criação, 28 dias (LENZ et al 2017). Entretanto, os peixes do trabalho anterior eram alimentados três vezes ao dia, fato que pode ter melhorado o consumo de ração e a conversão alimentar.…”
Section: Resultados E Discussõesunclassified